2018
DOI: 10.3389/fphys.2018.00981
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Function of Neuropeptides W/B Signaling System

Abstract: Neuropeptide W (NPW) and neuropeptide B (NPB) are two structurally and functionally related regulatory peptides, which are highly expressed in several brain regions and, additionally, in some peripheral tissues. Nevertheless, their distributions in the tissues are not similar. They act on target tissues via two subtypes of G protein-coupled receptors which are designated as NPBWR1 (GPR7) and NPBWR2 (GPR8), respectively, and possess different binding affinities. NPB activates NPBWR1, whereas NPW stimulates both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 66 publications
(229 reference statements)
2
26
0
Order By: Relevance
“…So far, we can only speculate about the function of this signaling system in the heart, because very little information is currently available in the literature. It has been demonstrated that NPB/W signaling system is involved in the regulation of blood pressure both at the central and peripheral levels [1]. Our finding demonstrating the presence of NPB within smooth muscle cells of coronary circulation supports the idea that NPB could be involved in regulation of coronary circulation.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…So far, we can only speculate about the function of this signaling system in the heart, because very little information is currently available in the literature. It has been demonstrated that NPB/W signaling system is involved in the regulation of blood pressure both at the central and peripheral levels [1]. Our finding demonstrating the presence of NPB within smooth muscle cells of coronary circulation supports the idea that NPB could be involved in regulation of coronary circulation.…”
Section: Discussionsupporting
confidence: 85%
“…The presence and tissue distribution of individual members of the NPB/W signaling system were studied by several working groups in the central nervous system, and detailed information is available in the literature [1]. It has been suggested that the NPB/W signaling system is involved in several central regulations including regulation of neuroendocrine functions; regulation of feeding activity; autonomic regulation; and activation of stress axis, pain sensation and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations